Dual efficiency enhancement in overall water splitting with defect-rich and Ru atom-doped NiFe LDH nanosheets on NiCo2O4 nanowires - Dao, Huyen Thi; Hoa, Van Hien; Sidra, Saleem; Mai, Mai; Zharnikov, Michael; Kim, Do Hwan (The chemical engineering journal, 2024)
The development of layered double hydroxides (LDHs) as bifunctional catalysts for efficient overall water splitting by controlling the composition and structure of the material remains challenging. In this study, defect-rich and Ru-doped NiFe LDH nanosheet shells on NiCo2O4 (NCO) nanowires were successfully synthesized using a hydrothermal method, followed by alkaline etching. The resulting def-Ru-NiFe LDH/NCO (def = defects) catalyst exhibited remarkable catalytic activity with overpotentials of 122 and 225 mV for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), respectively, at a current density of 10 mA cm−2. Density functional theory calculations demonstrated that atomic vacancy defects and the rational incorporation of Ru single atoms in def-Ru-NiFe LDH/NCO induced the regulation of the electronic structure and optimized the adsorption energies, thus enhancing the OER and HER performances. Particularly, an electrolyzer utilizing def-Ru-NiFe LDH/NCO exhibited exceptional performance, achieving cell voltages of 1.58 and 1.46 V in 1 M KOH at 25 and 75 °C, respectively. Moreover, the catalyst exhibited outstanding stability during 60 h of operation at a high applied voltage and temperature (75 °C). These results highlight the potential of def-Ru-NiFe LDH/NCO for hydrogen production.
Gesehen am 30.09.2024